Economic and Environmental Impact of Construction and Demolition in Green Buildings: A Case Study of Jordan - Albaali, Ghani; Shahateet, Mohammed Issa; Daoud, Hussam-edin; Saidi, Abdul Ghafoor (International Journal of Energy Economics and Policy, 2020)
This study aims to examine the impact of construction and demolition in green buildings in Jordan. It discusses the benefits that might be achieved as a result of the adoption of the green building in the construction projects, executed by the construction sector. The study highlights the importance of the reduction in waste resulting from the construction works, saving in water, energy and natural resources, as well as, the positive effects on the environment. The study utilizes a descriptive methodology based on survey analytical methods. It explores the several advantages that have been achieved in applying the building method in the construction of the WHO organization’s building at the economic and environmental levels. The study recommends taking several steps to activate the proposed incentives to support the adoption of the green building method by Jordanian construction companies, encouraging the engineering offices to consider the green building specifications in the design and the execution of building and the projects, increasing the awareness about the importance of the green building and its positive environmental effects. The study contributes to bridging the gap in the existing literature regarding energy savings and environmental benefits of construction and demolition in green buildings, which lacks applied research in developing countries. The results of this study are not limited to Jordan, but could easily be adopted by other developing countries. Keywords: Green building; construction works; energy and natural resources; Jordan JEL Classifications: Q42, Q51, Q56, Q57, O13 DOI: https://doi.org/10.32479/ijeep.10440